Smart Trolleys System For Smart Shopping - K. Gopinath; B. Sreedevi (Elementary Education Online, 2023)
The Internet of Things(IoT) is changing human lives by connecting everyday objects together. For example,A Super market is a place where customers come to purchase their daily using products and pay for that. When we go to shopping mart for shopping, we have to work for selecting the right product. Also after that, it is hectic to stand in line for Billing all the goods.Hence, we are proposing to develop a Smart shopping cart system that will keep the track of purchased product and also online transaction for Billing using RFID. The system will also give suggestions for products to buy based on user purchase history from a centralized system, every product in Mart will have RFID Transmitter and every cart will be having RFID Receiver attached to it. There will be a centralized system for the recommendation and online transaction and also we have a automatic Trolley control using WIFI, and the trolley can be controlled using mobile phone and ever one can control the trolley by connecting through hot spot and can easily controlled through the system.